Prevalence of Functional Disabilities and Associations Among Disabilities, Violence, and HIV Among Adolescents and Young Adults in Lesotho - Greta M. Massetti; Caroline Stamatakis; Sana Charania; Francis B. Annor; Catherine E. Rice; Jennifer Hegle; Puleng Ramphalla; Masechache Sechache; Mookho Motheo (Springer, 2024)
Abstract Introduction Lesotho has the second-highest prevalence of HIV. Despite progress in achieving HIV epidemic control targets, inequities persist among certain groups, particularly associations between disability, HIV, and violence. We assessed the prevalence of disability and examined associations between disability and HIV and violence using data from the 2018 Lesotho Violence Against Children and Youth Survey (VACS). Methods Lesotho VACS was a nationally representative survey of females and males ages 13-24. We assessed the associations between disability status and HIV, sexual risk behaviours, and violence using logistic regression, incorporating survey weights. Results Weighted functional disability prevalence was 14.1% for females (95% confidence interval [CI] 12.7-15.4) and 7.3% for males (5.3-9.2). Compared with females with no disabilities, females with disabilities had higher odds of being HIV positive (adjusted odds ratio [aOR] 1.92, 1.34-2.76), having transactional sex (aOR 1.79, 1.09-2.95), and experiencing any lifetime violence (aOR 2.20, 1.82-2.65), sexual violence (aOR 1.77, 1.36-2.31), emotional violence (2.02. 1.61-2.53), physical violence (aOR 1.85, 1.54-2.24), witnessing interparental violence (aOR 1.71, 1.46-2.01), and witnessing community violence (aOR 1.52, 1.26-1.84). Males with disabilities had higher odds of having transactional sex (aOR 4.30, 1.35-13.73), having recent multiple sex partners (aOR 2.31, 1.13-4.75), experiencing emotional violence (aOR 2.85, 1.39-5.82), and witnessing interparental violence (aOR 1.78, 1.12-2.84). HIV models for males did not converge due to low numbers. Conclusion Findings emphasize the importance of inclusion and accessibility for adolescents and young adults with disabilities in prevention and services for violence and HIV. Ending HIV in Lesotho depends on addressing the vulnerabilities that lead to potential infection including violence and ensuring equitable services for all.